2020
DOI: 10.33182/ml.v17i2.935
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus and Migration: Analysis of Human Mobility and the Spread of Covid-19

Abstract: Reactions, measures as well as discourses dealing with the current pandemic vary significantly across the world. While some countries were completely locked down, as was the case in Italy, some had claimed to have very few or no cases, as was the case in Turkey and Indonesia by March 10th, 2020. Nevertheless, the spread of COVID-19 from China has been clearly linked to those travelling from Wuhan in Hubei province in Central China. Therefore, it is important to understand the travel density/volume of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
120
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 23 publications
4
120
0
5
Order By: Relevance
“…The literature shows a significant effect of population density on the outbreak of infectious diseases (44). While a previous study (29) found no significant relationship between population density and total confirmed COVID-19 cases, there is a broader literature that shows an association between population density and the outbreak of infectious diseases (44).…”
Section: Datamentioning
confidence: 97%
See 4 more Smart Citations
“…The literature shows a significant effect of population density on the outbreak of infectious diseases (44). While a previous study (29) found no significant relationship between population density and total confirmed COVID-19 cases, there is a broader literature that shows an association between population density and the outbreak of infectious diseases (44).…”
Section: Datamentioning
confidence: 97%
“…We test this using four population characteristics of individual countries: Human Development Index (HDI), population aged over 65, mean household size and national population size. These variables have been selected based on recent studies that found them significant in explaining the COVID-19 outbreak at the early stages of its spread (8,29,46).…”
Section: Different Underlying Processes Characterise Types Of Spatialmentioning
confidence: 99%
See 3 more Smart Citations